Determination of morphology and immunophenotype of circulating lymphoma cells in patients with splenic marginal zone lymphoma using an anti-CD antibody microarray - A. N. Khvastunova; L. S. Al-Radi; O. S. Fedyanina; U. L. Julhakyan; N. M. Kapranov; A. O. Zakirova; S. A. Lugovskaya; E. V. Naumova; F. I. Ataullakhanov; S. A. Kuznetsova (Онкогематология)
We have studied the morphology and immunophenotype of circulating tumor cells isolated from peripheral blood of 22 patients with splenic marginal zone lymphoma and show that both of them are highly heterogeneous. Using a cell-binding microarray we have demonstrated that the circulating lymphoma cells are positive for CD19 (100 %), CD20 (100 %), CD22 (100 %), surface IgM (73 %), CD38 (23 %), CD5 (9 %), CD11c (36 %), CD103 (5 %), CD25 (32 %), CD23 (23 %) and these immunophenotypes are confirmed in all cases by flow cytometry.Higher surface density of lymphocyte binding onto anti-CD antibody microarray spots compared to blood smears permits to find circulating lymphoma cells even in leukopenic patients.